Proceedings of Fourth International Conference on Soft Computing for Problem Solving SocProS 2014 - International Conference on Soft Computing for Problem Solving Silchar, India) 2014; Das, Kedar Nath; Deep, Kusum; Pant, Millie; Bansal, Jagdish Chand; Atulya Nagar; SpringerLink (Online service). (New Delhi Springer, 2015)
This two volume book is based on the research papers presented at the 4th International Conference on Soft Computing for Problem Solving (SocProS 2014)and covers a variety of topics, including mathematical modelling, image processing, optimization methods, swarm intelligence, evolutionary algorithms, fuzzy logic, neural networks, forecasting, medical and healthcare, data mining, etc. Mainly the emphasis is on Soft Computing and its applications in diverse areas. The prime objective of this book is to familiarize the reader with the latest scientific developments in various fields of Science, Engineering and Technology and is directed to the researchers and scientists engaged in various real-world applications of Soft Computing.
Electronic reproduction.
Keywords: Soft computing -- Congresses; Problem solving -- Data processing -- Congresses; Electronic books